Rebuilding an enlightened world : folklorizing America - Ivey, Bill J. (Indiana University Press, 2018)
"Today, the long-assumed belief in the permanence of an enlightened world is suddenly open to challenge. Human rights, participatory government, and social justice are losing global influence, and the world of ordinary people is pushing back against Enlightenment conceits. Accumulated anger links Taliban, Tea Party, and Trump, threatening women's rights, social justice, and democracy. To understand and counteract the threat to these ideas, we must set aside embedded explanations and embrace a new frame of observation and tolerance grounded in the power of belief, legend, and tradition. In Rebuilding an Enlightened World, Bill Ivey explores how folklore offers a unique and compelling new way to understand the underlying forces disrupting the world today. If we are to salvage the best of the Enlightenment dream and build a better future, we must begin to listen, patiently and inquisitively, in order to interpret the customs, norms, and traditional practices that shape all human behavior."--Back cover.
Keywords: Cultural awareness : United States; Politics and culture : United States; Enlightenment : Influence; Folklore : Study and teaching; kulttuuri; kulttuurin muutos; politiikka; valistus (aatteet); kansanperinne; folkloristiikka; kultur; kulturförändring; politik; upplysning (idéer); folktradition; folkloristik; United States : Relations; United States : Cultural policy; Yhdysvallat; Förenta staterna